Applicability of the theory of business decision making based on the example of Serbian cultural tourism - Krasojević Branko; Holodkov Vladimir; Tomka Dragica (University Educons, Faculty of Sports and Tourism, Novi Sad, 2014)
Tourism is a complex system that must, theoretically, be observed through interdisciplinary studies, because it is practically connected to many aspects of modern civilization. In tourism, as a system, tangible and intangible values are included that are being and have been created by the nature, but also by activity and knowledge of people. Tourism is happening everywhere, sometimes it spontaneously arises and disappears unexpectedly. Tourism as a business system and a process does not involve mainly large and complex systems of functioning. The tourism industry is dominated by small and medium-sized enterprises, family businesses, constantly new and creative ideas. The biggest business systems are hotels and large tour operators. Therefore the destination of all levels occur - from the local destination to the world as a destination. Destinations are systems in which tourism is only a part of all events. The management of such a system is a complex, challenging and often unpredictable process. However, it seems that anybody can 'deal' in tourism, that tourism is easy to manage and to make the right business decisions. It often happens that tourism is not essentially managed by anyone, that it is left to itself, or to the individuals and small business units. In this paper, there is a research dilemma - whether the models of business decision-making are being applied in the cultural tourism of Serbia, by which means and with what results? The results of the work were obtained using analytical and synthetic methods of content analysis.